Fighting for her wolves eaudiobook A reverse harem paranormal romance. - West, Tara (Hungry for Her Wolves, 2019)
When lone wolf Annie Thunderfoot's human brother is threatened by a crazed shifter chieftain, she flies to Texas to diffuse the situation. She's thrust smack in the middle of a shifter civil war, and the insane chieftain is her mates' father. Annie's dreams of finding her fated mates are crushed when she realizes they are being manipulated by a madman. Before she can fight for the men who want to claim her, she must first uncover her alpha's dark past and convince him he's worthy of love. Her plans are put on hold when a tricky demon threatens her, forcing her to choose between fighting for love and saving her soul. Contains mature themes.